2022
DOI: 10.3390/pathogens11050556
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Manifestations of Multisystem Inflammatory Syndrome during the SARS-CoV-2 Pandemic

Abstract: The novel coronavirus SARS-CoV-2, which has similarities to the 2002–2003 severe acute respiratory syndrome coronavirus known as SARS-CoV-1, causes the infectious disease designated COVID-19 by the World Health Organization (Coronavirus Disease 2019). Although the first reports indicated that activity of the virus is centered in the lungs, it was soon acknowledged that SARS-CoV-2 causes a multisystem disease. Indeed, this new pathogen causes a variety of syndromes, including asymptomatic disease; mild disease;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…More importantly, our results showed that male patients had significantly higher serum concentrations of VEGF, IFNγ, IL-13, and IL-5 than female patients. This is in line with previous studies demonstrating a stronger response in cytokines and chemokines in SARS-CoV-2-infected male than in female patients [ 6 , 13 ]. Differences in the expression of cytokines and chemokines secondary to infection are partially yet substantially controlled by sex hormones, which modulate the innate immune function at various stages of human life concurrent with hormonal changes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More importantly, our results showed that male patients had significantly higher serum concentrations of VEGF, IFNγ, IL-13, and IL-5 than female patients. This is in line with previous studies demonstrating a stronger response in cytokines and chemokines in SARS-CoV-2-infected male than in female patients [ 6 , 13 ]. Differences in the expression of cytokines and chemokines secondary to infection are partially yet substantially controlled by sex hormones, which modulate the innate immune function at various stages of human life concurrent with hormonal changes.…”
Section: Discussionsupporting
confidence: 93%
“…SARS-CoV-2 infection induces over-production of pro-inflammatory cytokines and chemokines as a defense mechanism against the viral infection. On the other hand, a dysregulation, i.e., hyper-inflammation, results in cytokine release syndrome (CRS) leading to apoptosis of immune cells, impaired cytotoxic function, and tissue damage [ 13 ]. More importantly, our results showed that male patients had significantly higher serum concentrations of VEGF, IFNγ, IL-13, and IL-5 than female patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has the high transmissibility and moreover, the ability to escape from immune response, caused by vaccination or natural infection [ 16 ]. In addition, its pathogenicity is much lower and it causes less hospitalization, lethal outcomes and severe cases [ 17 , 18 ]. However, it should be noted, in comparison with Delta variant, Omicron increased a number of hospitalizations among children aged 5–11 [ 19 , 20 ].…”
Section: Characteristics Of Sars-cov-2mentioning
confidence: 99%
“…Due to an aggregation of uncleaved angiotensin II, the stimulated inflammatory cells cause cytokines synthesis and secretion (cytokine storming), leading to widespread tissue injuries [ 38 ]. In some cases severe acute respiratory syndrome coronavirus can form the HGSIP (elevated CRP, fibrinogen, procalcitonin, D-dimer, ferritin, IL-6, erythrocyte sedimentation rate, elevated neutrophils, reduced lymphocytes, low albumin), whose consequences include Multisystem Inflammatory Syndrome (MIS) affected children (MIS-C) and adults (MIS-A) with inflammation of a variety of organ systems, including the heart, lungs, brain, kidneys, gastrointestinal system, skin, and eyes [ [39] , [40] , [41] ]. However, criterial signs of the SIRS may be absent.…”
Section: Low- and High-grade Systemic Inflammatory Response Phenotypesmentioning
confidence: 99%